Influence of imperfection on amplitude and resonance frequency of a reinforcement compositionally graded nanostructure. Issue 6 (2nd November 2021) - Hashemi, Hamid Reza; Alizadeh, As'ad; Oyarhossein, Mohammad Amin; Shavalipour, Aghil; Makkiabadi, Mahmoud; Habibi, Mostafa
Abstract : This article investigates the influences of nonuniform imperfection on the dynamic amplitude and resonance frequency of the nanoshell reinforced with graphene nanoplatelet (GNP). The novelty of the current study is to consider the effects of porosity, thermal loading and graphene platelet reinforced composites on the dynamic behavior of the nanostructure. Three-length scale parameters ( l 0  =  5 h, l 1  =  3 h, l 2  =  5 h) in the modified strain gradient theory (MSGT) show a better agreement with MD simulation in comparison with other theories. Finally, the effects of different factors on the dynamic amplitude and resonance frequency of the porous nanostructure are examined in detail.